ANALISIS PENGARUH PENGALAMAN AUDITOR, KOMITMEN PROFESIONAL, ORIENTASI ETIS DAN NILAI ETIKA ORGANISASI TERHADAP PERSEPSI DAN PERTIMBANGAN ETIS (Studi Kasus Pada KAP di Kota Malang). - Abdur Rohman; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
ABSTRACTThis research is conducted with the purpose of: 1) To know whether experience,professional commitment, ethical orientation and organizational ethical valuessimultaneously affect the perceptions and ethical considerations of Auditors PublicAccountant Office in Malang, 2) Is experience, professional commitment, ethical orientationand value Organization affects partially on the perception and ethical considerations AuditorPublic Accounting Firm in Malang.Populasi used in this study is KAP Kotamalang.Pemilihan sample using purposive sampling.Berdasarkan criteria, obtained 50 KAPwhich became the sample in this research.Method used In this study using multiple linearregression method.Based on the results of the analysis can be put forward severalconclusions as follows: 1) F test results show that the variables of experience auditors,professional commitment, ethical orientation and ethical values of the organizationsimultaneously affect perceptions and per Ethical scale.2) The results of t test show that forthe variable experience of auditors partially have no significant effect on the perception andethical considerations.3) Professional commitment variable partially significant effect on theperception and ethical considerations.4) variable ethical orientation partially significanteffect on Perceptions and ethical considerations. 5) organizational ethical values partiallyhave significant influence on perceptions and ethical considerationsKeywords: Auditor Experience, Professional Commitment, Ethical Orientation And Value ofOrganizational Ethics and Perceptions and Ethical Considerations ABSTRAC